Diet preference and growth performance in weanling pigs fed diets with morinda citrifolia (noni) - C Feoli; Joe D Hancock; Keith C Behnke (Kansas Agricultural Experiment Station Research Reports, 2008)
Two experiments were conducted to determine the effects of adding 5% Morinda citrifolia (noni; Morinda Agricultural Products, Orem, UT) to diets for weanling pigs. In Exp. 1, 48 pigs (initially 9.3 lb) were used in a 29-d preference study. There were 6 pigs per pen and 8 pens total. The pens were equipped with 2 identical feeders (for diets without and with noni puree), and position of the feeders was switched each afternoon to prevent feeder location from affecting diet consumption. The diets were corn-soybean meal-based, pelleted, and had 1.8% lysine for d 0 to 5, 1.6% lysine for d 5 to 15, and 1.4% lysine for d 15 to 29. Feed and water were consumed on an ad libitum basis. No differences were noted among diets without and with noni for pelleting ease and pellet durability index (PDI). Feed intake was increased for d 0 to 5 (0.11 vs. 0.23 lb/d, P<0.05) and d 0 to 15 (0.15 vs. 0.37 lb/d, P<0.006) when noni was added to the diets. However, this effect disappeared for d 15 to 29 so that overall feed intake was not different (0.40 vs. 0.50 lb/d, P>0.39) for d 0 to 29. In Exp. 2, 96 pigs (initially 14.8 lb) were used in a 29-d growth assay. There were 6 pigs per pen and 8 pens per treatment. The diets were the same as those used in the first experiment. Results indicated no differences (P>0.29) in ADG, ADFI, and F/G for d 0 to 5 and 0 to 15 between pigs fed diets without and with noni. However, for d 15 to 29 and overall (d 0 to 29), ADG and ADFI were decreased (P<0.04) for pigs fed diets with noni compared with the control. In conclusion, there was a preference for diets with noni for the first 15 d of the preference study. In the growth assay, prolonged feeding of diets with noni resulted in reduced feed intake and, ultimately, decreased rate of gain.; Swine Day, 2008, Kansas State University, Manhattan, KS, 2008
Keywords: Swine day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-074-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1001; Diet preference; Morinda citrifolia; Noni; Weanling pigs